Dodd-Frank : what it does and why it's flawed - Peirce, Hester (Mercatus Center at Georg Mason University ArlingtonUS, 2012)
Looks at the Dodd-Frank Wall Street Reform and Consumer Protection Act and asks whether it is an effective response to the US financial crisis.